Problems of Commercializing Innovations in the Aspect of Interests Coordination for the Subjects of the Intellectual Product Market - Irina TRUBINA; Olga RUDAKOVA; Elena SEMYONOVA; Aleksander ZAKHAROV; Lyudmila KUZNETSOVA (Communications of International Proceedings, 2020)
The article is devoted to the research of processes for commercializing innovations taking into account interests coordination for the subjects of an innovation cycle. The purpose of the research is to characterize the current problems of the market for intellectual products, within which the commercialization of innovations is carried out. Based on the analysis of official statistical information, trends in the development of the Russian innovation market were identified. It is noted that the demand in the domestic market for intellectual property resulting from private businesses is relatively low. It is revealed that the activity of the private sector for investing in the innovation sphere is inferior to the state. The article suggests systematic marketing research of consumers ' requests for innovative products, the formation of a new mechanism for synchronizing financing at the stages of the innovation cycle, expanding the practice of concluding license agreements, developing innovation infrastructure, stimulating investment in science and training innovative personnel.
Keywords: Innovation; Innovation Activity; Innovation Management; Intellectual Resource.